ANALYSIS OF THE READINESS TOWARDS THE IMPLEMENTATION OF ISO STANDARD 9001: 2015 IN THE COMPANY OF HEAVY EQUIPMENT - Suhendris Suhendris; Dana Santoso Saroso (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
Heavy equipment market in Indonesia is very large, the opportunity to increase heavy equipment business is wide open, and all competitors provide the best products and services for their customers. For this reason, companies need to develop an international standard system. The system is known as Quality Management System (QMS) and developed in ISO 9001: 2015 standard certification. ISO 9001 is a standard that contains the requirements of the Quality Management System issued by the International Organization for Standardization (IOS). Companies that become the object of research is heavy equipment company engaged in the sale of heavy equipment and after-sales service. The problem that is going on in this company is that there is a lot of down payment for the purchase of units and spare parts that cannot be billed due to the documents that are related to the purchase process, many of which are non-existent and also missing, besides that there are also many complaints regarding the availability of spare parts and service, this is one of the indirect impacts of not implementing QMS ISO 9001: 2015. The research objective is to evaluate the current condition of the Heavy Equipment Company and assess the readiness of the Company in meeting ISO 9001: 2015 standards. The method used is Gap Analysis requirements of ISO 9001: 2015. Calculation on Gap Analysis uses a checklist made based on the requirements of ISO 9001: 2015, and the results will show how much the readiness of the Heavy Equipment Company meets the ISO 9001: 2015 standard.